Cyber Laws and Cyber Security : The Jurisprudence and Judicature - Prakash, K. Bhanu; Reddy, P. Siva (Indian Journal of Computer Science, 2018)
With the advancement and use of internet, the number of users have increased manifold. People are using the internet for their daily needs, financial transactions, networking etc. This poses a risk to them if the applications and networks that they are using are not secure enough. They are prone to financial frauds and cyber attacks of various kinds. In this light, it becomes important to have a legal framework to address growing cyber crimes. This paper discusses cyber threats and the legal frameworks that exist in India to deal with the problem.